2003
DOI: 10.1176/appi.ajp.160.10.1863
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of White Matter Structure in Velocardiofacial Syndrome: A Diffusion Tensor Imaging Study

Abstract: This study demonstrates that alterations of white matter tract structure occur in velocardiofacial syndrome. Reduced white matter anisotropy was observed in individuals with velocardiofacial syndrome in areas previously implicated in the neurocognitive phenotype of velocardiofacial syndrome. The finding of aberrant parietal white matter tracts as well as aberrant frontotemporal connectivity in velocardiofacial syndrome and in previous schizophrenia studies may be associated with increased vulnerability for dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
86
2
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(102 citation statements)
references
References 39 publications
(52 reference statements)
12
86
2
2
Order By: Relevance
“…Starting with the visuo-spatial processing network (VSPN), increased activation in the medial parietal lobe is indicative of atypical connectivity involving the left precuneus and posterior cingulate regions. In light of previous structural MRI findings reporting that poor arithmetic abilities in 22q11DS correlate with reduced fractional anisotropy values, particularly on the left parietal tracts (Barnea-Goraly et al, 2003, the increased activity we observed in the VSPN may be interpreted as the signature of functional dysconnectivity in the dorsal "where" stream, often hypothesized to underlie the characteristic visuo-spatial dysfunctions in children with 22q11DS (Lajiness-O'Neill et al, 2005;Van Aken et al, 2009). Consistently, parietal lobe gray matter volumes are often found to be reduced in children with 22q11DS (Eliez et al, 2000;Kates et al, 2001), and a recent report suggests that gyrification in the precuneus/PCC regions is more affected in children with 22q11DS as a result of congenital heart defects associated with this deletion syndrome (Schaer et al, 2009b).…”
Section: Discussionsupporting
confidence: 65%
“…Starting with the visuo-spatial processing network (VSPN), increased activation in the medial parietal lobe is indicative of atypical connectivity involving the left precuneus and posterior cingulate regions. In light of previous structural MRI findings reporting that poor arithmetic abilities in 22q11DS correlate with reduced fractional anisotropy values, particularly on the left parietal tracts (Barnea-Goraly et al, 2003, the increased activity we observed in the VSPN may be interpreted as the signature of functional dysconnectivity in the dorsal "where" stream, often hypothesized to underlie the characteristic visuo-spatial dysfunctions in children with 22q11DS (Lajiness-O'Neill et al, 2005;Van Aken et al, 2009). Consistently, parietal lobe gray matter volumes are often found to be reduced in children with 22q11DS (Eliez et al, 2000;Kates et al, 2001), and a recent report suggests that gyrification in the precuneus/PCC regions is more affected in children with 22q11DS as a result of congenital heart defects associated with this deletion syndrome (Schaer et al, 2009b).…”
Section: Discussionsupporting
confidence: 65%
“…Reduced white matter volume in the right cerebellum (Eliez et al 2000) and bilateral frontal, parietal and temporal regions and the external capsules as well as increased fractional anisotropy in posterior brain regions were also reported (Kates et al 2001(Kates et al , 2004van Amelsvoort et al 2001van Amelsvoort et al , 2004Barnea-Goraly et al 2003;Simon et al 2005). Simon et al (2005) suggested that increased fractional anisotropy in the posterior brain regions may be indicative of corpus callosum displacement due to enlarged cerebral ventricles in individuals with 22q11DS.…”
Section: Brain Morphology In 22q11ds Casesmentioning
confidence: 91%
“…149 Moreover, myelination of the prefrontal cortex has been observed to occur in late adolescence and early adulthood, which is typically the age of onset of schizophrenia, 7,118,123 providing an indication of the importance of myelination for the continued maturation and normal functioning of the brain and the role of dysmyelination for the pathological pathways of the disorder.…”
Section: Further Evidence For the Role Of Oligodendrocytes And Myelinmentioning
confidence: 99%